2017
DOI: 10.18203/2394-6040.ijcmph20175360
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of gender preference among women of Belagavi: a cross sectional study

Abstract: Background: Sex ratio in India, has always remained unfavorable to females. Changes in the sex ratio, reflects the underlying socioeconomic, cultural patterns of a society. A number of factors influence the relative benefits and costs of sons and daughters and ultimately the parent’s gender preferences. Objective was to study the factors that determine gender preferences among women of reproductive age group and to formulate preventive measure against gender bias.Methods: A cross-sectional study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
(9 reference statements)
1
5
1
Order By: Relevance
“…Muslims had a higher SPI as compared to Hindus and Christians which was similar to the results obtained by Kanyadi S and Kulkarni R in their study in Belagavi 17 and by Asghar M et al 18 who conducted a study among Manipuri Muslims. The probable reason could be their minority status and the overall lower education levels of the females among the Muslim population.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Muslims had a higher SPI as compared to Hindus and Christians which was similar to the results obtained by Kanyadi S and Kulkarni R in their study in Belagavi 17 and by Asghar M et al 18 who conducted a study among Manipuri Muslims. The probable reason could be their minority status and the overall lower education levels of the females among the Muslim population.…”
Section: Discussionsupporting
confidence: 87%
“…10 Son preference was found to be more among mothers having a female child in a study done by Kanyadi S and Kulkarni R in Belgavi. 17 In a study by Asghar M, Murry B et al son preference was seen among mothers belonging to higher socio economic status. 18 Roy A and Biswas R in a study conducted in West Bengal reported a higher son preference among younger mothers between 18 and 24 years of age, mothers belonging to lower socio economic status and mothers who did not have a male child.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Socio-cultural factors like religion, occupation of women, literacy status, socioeconomic status influenced son preference according to a study conducted in Belagavi. 6 Unlike other similar studies conducted, religion and type of residence, were not found to be significantly associated with gender preference. The most common reason cited by the participants in our study for the male preference was propagation of family name, support of old age and no dowry burden which was similar to studies conducted in Madhya Pradesh 5 and Belagavi.…”
Section: Discussioncontrasting
confidence: 56%
“…The most common reason cited by the participants in our study for the male preference was propagation of family name, support of old age and no dowry burden which was similar to studies conducted in Madhya Pradesh 5 and Belagavi. 6 Similarly a study at Bareilly revealed that 80% females were aware of prenatal sex determination and 67% unaware of PNDT Act. 7 A study which was conducted by found that 95% of the pregnant women were aware of the availability of a method for intrauterine sex determination.…”
Section: Discussionmentioning
confidence: 99%